MEMBANGUN MODEL YURIDIS KOPERASI SYARIAH KOPKARDOS DI UNISBA SEBAGAI PERGURUAN TINGGI ISLAM TERKEMUKA DALAM RANGKA PEMBERDAYAAN ANGGOTA - Wiyanti, Diana (LPPM Unisba, 2011)
Lecturer and employee Cooperative (Kopkardos) in Unisba was built since 1978. But operation and base founding was not yet based on the Islamic principles. This research had a purpose to know of institutional status of Kopkardos in Unisba whether according with the current provisions, operation of Kopkardos in Unisba and yuridical model Islamic Cooperation for Kopkardos in Unisba. This research was used descriptive analysis and the juridical approach is normative method with the data analysis of normative qualitative. The result of this research are Kopkardos Unisba was legal agency since 1978, but its management operation used conventional system , since 2010 The Kopkardos was Procesed to the Islamic cooperative Through the co-operation with Islamic financial agency , yuridical model for islamic cooperative in Unisba is based on the provisions of the Cooperative Ministers decision of Republic Indonesia No 91/Kep/M.KUKM/IX/2004 About the Guidance of the Implementation of the Activity efforts the cooperation of the Service of Islamic Finance.